2021
DOI: 10.1039/d0sc06528e
|View full text |Cite
|
Sign up to set email alerts
|

Molecular recognition of SARS-CoV-2 spike glycoprotein: quantum chemical hot spot and epitope analyses

Abstract: Due to the COVID-19 pandemic, researchers have attempted to identify complex structures of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike glycoprotein (S-protein) with angiotensin-converting enzyme 2 (ACE2) or...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 82 publications
(148 reference statements)
6
56
0
Order By: Relevance
“…Previous research on the interaction between SARS-CoV-2 S-protein RBD and ACE2 with FMO calculation 46 also showed that the interaction sites of hACE2 on RBD could be concentrated in these two regions.…”
Section: Toc Graphicmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous research on the interaction between SARS-CoV-2 S-protein RBD and ACE2 with FMO calculation 46 also showed that the interaction sites of hACE2 on RBD could be concentrated in these two regions.…”
Section: Toc Graphicmentioning
confidence: 85%
“…Interaction analyses between S-protein and hACE2 or B38 Fab antibodies using the FMO method have been reported [45][46][47] . This study focused on 12 antibodies/peptides (LCB1 27 , LCB3 27 , C105 23 , COVA2-04 21 , BD-604 26 , CB6 17 , B38 17 , BD-629 26 , C102 22 , CC12.3 19 , CC12.1 19 , and CV30 17 ) and analyzed the interactions between these antibodies/peptides and the RBD using the FMO method.…”
Section: Toc Graphicmentioning
confidence: 99%
“…On the other hand, the main contribution of Asn501 is ES with surrounding amino acid residues (Tyr41, Lys353, Gly354, etc.). In a previous study, it was reported that the N501Y mutation enhances the ability of S protein to bind to ACE2 by acquiring more hydrogen bonds and XH/ interactions than WT 49 .…”
Section: Spike (S) Proteinmentioning
confidence: 99%
“…Due to the large negative charge of ACE2, hydrogen bonds and XH/ interactions, which are key interactions in molecular recognition of S protein, are hidden by ES interactions of the charged residues. However, the hydrogen bond can be easily interpreted by analyzing the ES and CT terms of PIEDA, and the XH/ interaction can be easily interpreted by analyzing the DI term 49 . In addition, we performed PIEDA analysis of the mutant residues of S protein, Lys417 and Asn501, in the South African and Brazilian mutants and the surrounding residues (Figures 15 b,c).…”
Section: Spike (S) Proteinmentioning
confidence: 99%
“…Weak hydrogen bonds (HBs) involving CH bonds as donor groups and O as acceptor atoms have been evidenced decades ago for crystalline organic molecules. [1][2][3] Since then, they have a recognized role in biology and in several areas of chemistry [4][5][6][7] thanks to their implications in molecular properties like crystal packing, [8,9] supramolecular assembly's formation, [10] conformational states, [8,11,12] host-guest interactions and molecular recognition, [13,14] organic-inorganic hybrid networks [15] and drug discovery [16] to name a few.…”
Section: Introductionmentioning
confidence: 99%